MAPPING SPREAD OF COVID-19 CASES IN TODDLERS AND CHILDREN AT CENTRAL JAVA USING K-MEANS CLUSTER: Pemetaan Persebaran Kasus COVID-19 pada Balita dan Anak di Jawa Tengah Menggunakan K-Means Cluster - Evina Widianawati; Widya Ratna Wulan; Anis Tri Wahyuni; Faik Agiwahyuanto (Universitas Airlangga, 2023)
Background: Toddlers and children under 12 are still easily sick, particularly during the COVID-19 epidemic. The high number of COVID-19 cases in toddlers and children in Central Java Province must be monitored to prevent transmission to toddlers and children still susceptible to the disease. Purpose: The purpose of this study was to map the spread of COVID-19 cases in toddlers aged 0-5 years and children aged 6-11 years in the province of Central Java using the K-means cluster Methods: This was a descriptive observational study with a cross-sectional design. Data on COVID-19 cases in children 6-11 years and toddlers 0-5 years from 35 cities in Central Java in 2020-2021 were analyzed using the K-means cluster. The K-means cluster was used to cluster low, medium, and high cases and then map the spread of COVID-19. Results: Semarang, Semarang Regency, Boyolali, Klaten, Surakarta, and Banyumas became high cluster areas in cases of COVID-19 toddlers and children in 2021. Based on the mapping data, COVID-19 spread in young children and toddlers in 2020 and 2021 followed a nearly identical pattern. The high zone of COVID-19 in toddlers and children mostly had a higher total population, healthcare facilities, and population density than the medium and low zones. Conclusion: Semarang City, Semarang Regency, Boyolali, Klaten, Surakarta, and Banyumas should be looking for COVID-19 cases in toddlers and young children.